63.0k views
4 votes
Which expression is equivalent to ( 4mn / m^-2n^6)^-2

a. n^6 / 16m^8
b. n^10 / 16m^6
c. n^10 / 8m^8
d. 4m^3 / n^8

1 Answer

3 votes

Here are a few rules with exponents that apply here:

  1. Raising a power to a power:
    (x^m)^n=x^(m*n)
  2. Dividing exponents of the same base:
    (x^m)/(x^n)=x^(m-n)
  3. Converting negative exponents to positive ones:
    x^(-m)=(1)/(x^m)\ \textsf{and}\ (1)/(x^(-m))=x^m

Firstly, solve the outer exponent:


((4mn)/(m^(-2)n^(6)))^(-2)=(4^(-2)m^(-2)n^(-2))/(m^(-2*-2)n^(6*-2))=(4^(-2)m^(-2)n^(-2))/(m^4n^(-12))

Next, divide:


(4^(-2)m^(-2)n^(-2))/(m^4n^(-12))=4^(-2)m^(-2-4)n^(-2-(-12))=4^(-2)m^(-6)n^(10)

Next, convert the negative exponents:


4^(-2)m^(-6)n^(10)=(n^(10))/(4^2m^6)=(n^(10))/(16m^6)

Your final answer is n^10/16m^6 , or B.

User AndreyIto
by
5.9k points